PENYULUHAN TENTANG TEKNIK PEMASARAN HASIL TANGKAPAN NELAYAN BAGI MASYARAKAT NELAYAN KEPUTIH TIMUR GANG POMPA KECAMATAN SUKOLILO SURABAYA: EDUCATION ON MARKETING TECHNIQUES FOR FISHERMEN'S CATCHES FOR THE FISHING COMMUNITY OF KEPUTIH TIMUR GANG POMPA, SUKOLILO DISTRICT, SURABAYA - Akhmad, Ekka Pujo Ariesanto; Setiono, Beni Agus; Purwanto, FX Adi; Purwiyanto, Didik; Hidayat, Sapit; Prawirosastro, Carlos L. (Jurnal Pengabdian Masyarakat Pesisir, 2025)
The extension aims to increase the fishing community's understanding of effective marketing techniques, so that the catch can be better and profitably marketed. Thus, it is hoped that fishing communities can optimize their catch and increase economic well-being through appropriate marketing strategies. As such, this extension is expected to provide more in-depth knowledge on how to market catches efficiently, as well as build a strong marketing network between fishermen and consumers.In addition, this extension will also address the importance of utilizing information technology in marketing, such as the use of social media and e-commerce platforms, to reach a wider market. Furthermore, workshops will be organized to train fishermen on creating appealing online profiles and engaging content that highlights the quality and sustainability of their catches, fostering a direct connection with consumers